1985
DOI: 10.1111/j.1365-3024.1985.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Site potential for challenge attrition in mice, rats and guinea pigs vaccinated with irradiated cercariae of Schistosoma mansoni

Abstract: The potential sites of attrition of a challenge population of schistosomes have been investigated in mice, rats and guinea pigs vaccinated with irradiated cercariae of Schistosoma mansoni, by the use of challenge regimens that permit sequential site elimination. Vaccinated mice showed significant immunity to a percutaneous cercarial challenge, but were only marginally resistant to an i.v. challenge with healthy lung stage worms. Vaccinated rats and guinea pigs differed from mice, in that they were able to medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…It has been questioned whether parasites detectable by autoradiography in the lungs are alive or dead (McLaren et al 1985). Our morphological observations show parasites, detected on the basis of their radioactivity, to be structurally intact and demonstrate the validity of the autoradiographic quantification of schistosomula in the lungs (Dean et al 1984, Wilson et al 1986).…”
Section: Vaccinated Micesupporting
confidence: 53%
“…It has been questioned whether parasites detectable by autoradiography in the lungs are alive or dead (McLaren et al 1985). Our morphological observations show parasites, detected on the basis of their radioactivity, to be structurally intact and demonstrate the validity of the autoradiographic quantification of schistosomula in the lungs (Dean et al 1984, Wilson et al 1986).…”
Section: Vaccinated Micesupporting
confidence: 53%
“…The parasites were then washed three times and examined on a Leitz fluorescence microscope. Fluorescence was quantified using a fluorimeter as described previously (Pearce et al 1985).…”
Section: Immunofluorescencementioning
confidence: 99%
“…While parasitological studies indicate that skin stage schistosomula are vulnerable to resistance mechanisms in immunized mice (Miller & Smithers 1980, Smithers & Gammage 1980, McLaren Pearce & Smithers 1985, recent experiments utilizing autoradiography or histology (Mastin, Bickle & Wilson 1983) to track the migration of individual parasites of a challenge infection within the immunized host suggest that lung and or post-lung, pre-adult stages of the parasite may be the major targets of the protective immune response in uiuo. However such a premise is not compatible with data derived from in uitro studies which have shown that soon after penetrating the skin, schistosomula acquire several mechanisms for evading the immune response (McLaren 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that laboratory rodents vaccinated with highly irradiated cercariae of Schistosoma mansoni develop significant protection against a challenge population of worms, and that resistance depends upon specific immunological mechanisms (Smithers & Doenhoff 1982, Dean, Bukowsky & Clark 1981, James, Labine & Sher 198 1, Sher et al 1982, Ford et al 1984, McLaren, Pearce & Smithers 1985. The rat and mouse models of vaccine-induced immunity have without doubt, received most attention with respect to dissection of the sites and mechanisms of challenge elimination, but the reintroduction of the guinea-pig as an alternative laboratory system (Pearce & McLaren 1983 a,b), has now revealed that challenge attrition does not necessarily occur at the same point along the migratory pathway of the parasite in every laboratory rodent .…”
Section: Introductionmentioning
confidence: 99%